Health Care Provider Stigma on People Living with HIV/AIDS (PLWHA) in Bandung - Angga Wilandika (Jurnal Keperawatan, 2019)
Healthcare providers’ stigma to people lived with HIV and AIDS (PLWHA) may cause a decreasing both in quality care and quality of life. Assessment on health care provider’s stigma needs to be measured in order to determine the stigma management strategy. This study aimed to identify psychometric scale and health care providers’ stigma of PLWHA. The design of this study was a quantitative analytic with cross-sectional approach. A total of 30 health care providers of Puskesmas were involved in this study. Psychometric analyses were performed to assess the reliability of the instruments. The data were analyzed using a descriptive analysis. The results of the stigma scale of health care providers were found that most (60%) of health care providers consisting of nurses, doctors, midwives, nutritionists have a high stigma against PLWHA. The high stigma against PLWHA may bring negative impact on health care services to PLWHA. Therefore, measurements of HIV-related stigma among health care providers need to be done, so that the policy-makers can formulate strategies to prevent the stigma of health care providers.Keyword: Discrimination, Health Care Providers, PLWHA, Stigma